2004
DOI: 10.1128/cdli.11.6.1054-1059.2004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Multiplexed Fluorescent Microsphere Immunoassay for Detection of Autoantibodies to Nuclear Antigens

Abstract: Antibodies to extractable nuclear antigens (ENA) are found in a variety of collagen vascular diseases. Determining the individual specificities of these antibodies is extremely useful in establishing the disease diagnosis and in some cases the prognosis. With a multiplexed fluorescent microsphere immunoassay, reactivity to five of the most diagnostically useful ENA was measured in 249 serum samples, including samples from 56 patients previously documented to have systemic lupus erythematosus (SLE). Results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 28 publications
2
47
0
Order By: Relevance
“…For example, serum concentration can alter the standard curve, and some studies revealed that human sera may contain heterophilic antibodies that directly bind to beads causing immunoassay interference. 49,106,156 Methods including dilution of sera and inactivation of complement in a HLA BBMA prevented false-negative reactions caused through a "prozone" effect. 158 Nonspecific binding of antibodies to microspheres causing false-positive reactions was also noted in another study.…”
Section: Sample and Assay Optimizationmentioning
confidence: 99%
“…For example, serum concentration can alter the standard curve, and some studies revealed that human sera may contain heterophilic antibodies that directly bind to beads causing immunoassay interference. 49,106,156 Methods including dilution of sera and inactivation of complement in a HLA BBMA prevented false-negative reactions caused through a "prozone" effect. 158 Nonspecific binding of antibodies to microspheres causing false-positive reactions was also noted in another study.…”
Section: Sample and Assay Optimizationmentioning
confidence: 99%
“…Multiplex assays based on fluorescent microbead flow cytometry and microarray systems have proven to be powerful tools, supporting greater throughput analysis and more comprehensive testing of multiple patient samples (4)(5)(6)(7)(8)(9)(10)(11). The novel detection technology presented in this study employs fluorescence-coded microbeads detected by a multicolor fluorescence image-capture based system with novel pattern recognition algorithms for multiplex testing (12).…”
mentioning
confidence: 99%
“…Very elevated titers of anti-Ro antibodies may be useful in the assessment of disease activity especially in patients that do not present with elevated titers of antidsDNA autoantibodies. In another recent study, with a multiplexed fluorescent microsphere immunoassay, reactivity to five of the most diagnostically useful ENA was measured in 249 serum samples, including samples from 56 patients previously documented to have SLE (Martins et al 2004). Significant concentrations of 5 autoantibodies measured by the multiplexed assay in 56 SLE patients were similar to ours, except for RNP, where we had a lower frequency (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…The multiplex bead array system has recently been utilized for autoantibody detection in various autoimmune diseases (Martins et al 2004). Thus, in our previous study, we compared the specificity and sensitivity of the recognition of ANA and 9 autoantibodies by the AtheNA system to the established ELISA method.…”
Section: Discussionmentioning
confidence: 99%